Exome sequencing of a Pakistani family with spastic paraplegia identified an 18 bp deletion in the cytochrome B5 domain of FA2H. (1st February 2021) - Abbas, Safdar; Brugger, Beatrice; Zubair, Muhammad; Gul, Sana; Blatterer, Jasmin; Wenninger, Julian; Rehman, Khurram; Tatrai, Benjamin; Khan, Muzammil Ahmad; Windpassinger, Christian
ABSTRACT: Hereditary spastic paraplegias (HSPs) are a diverse class of neurodegenerative disorders that mainly affect the corticospinal tract of the body and result in various clinical conditions such as lower limb spasticity and muscle weakness in the lower extremities. Worldwide, more than 70 chromosomal loci/genes have been reported to be associated with HSPs, out of which, six genes viz., ATL1, FA2H, GJC2, AP4E1, ALDH18A1 and ATP13A2 have been mapped in Pakistani families. In the present genetic study, we report on a large consanguineous Pakistani family with a complex form of HSP segregating with a 18 bp deletion in the first exon of the Fatty Acid 2-Hydroxylase ( FA2H ) gene (NM_024306.5:c.159_176del). The identified in-frame deletion results in loss of six amino acids (p.Arg53_Ile58del) within the cytochrome B5 domain of the protein. FA2H is required for alpha-hydroxylation of free fatty acids to form alpha-hydroxylated sphingolipids. Its cytochrome b5-like heme-binding domain, which spans from residues 15 to 85, imparts the redox activity to FA2H. This mutation has previously been reported in a Pakistani family presenting with a similar form of complex HSP. Together with our findings the pathogenic role of the observed variant is further supported. Mutation studies on additional Pakistani families for FA2H will further elucidate its mutational spectrum, which may help in developing a prenatal diagnostic test for Khyber Pakhtunkhwa resident Pakistani families.